DEBATES IN POLITICAL ANTHROPOLOGY AND THEIR SIGNIFICANSE FOR POLITICAL THEORY - Поліщук, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The key debates in political anthropology are considered in the article, namely the opposition between adaptationist and political theories, substantivism and formalism, homo sociologicus and homo economicus models. The main arguments used in these debates are given and their significance for political theory is outlined.